Local self-government in the structure of Russian statehood: problems and perspectives - O. L. Kazantseva; E. V. Kuzina (Правоприменение, 2022)
Essay. The subject of this research is to provide an elaborate analysis of current municipal reform in the RF and assess its impact on the self-government place, the role and development trends within the system of the Russian statehood. This paper aims either prove or disprove a hypothesis about the impact of adopted legal regulations on local self-government in the RF in view of the amendments to the RF Constitution, and make a contribution to scientific understanding of this issue.Methodology. The research methodology is built by combining such methods of scientific knowledge as analysis (to study normative legal acts on the research topic), synthesis (to analyse theoretical sources and make generalizations), comparative legal method (to study and compare legal norms), logical method (to identify the peculiarities of the research object), system-structural approach (to define the role of local self-government in the Russian statehood), the method of legal hermeneutics (to provide an interpretation of legal documents) and the synergistic method which allowed to analyse the system of local government in cooperation with state authorities.Results. Local self-government shall be recognized as the basis of a democratic regime and present-day Russian statehood. The adoption of the 1993 Constitution resulted in numerous normative acts which regulate the system of local self-government, including The Federal Law of October 6, 2003 No. 131-FZ “On the General Principles of Local Self-Government Organization in the Russian Federation”. However, regular changes to this law regarding local self-government have raised a number of concerns about uncertainty and contradictions in the legal system. Thus, along with positive effects of ongoing reforms, there are some negative trends including current tightening of local self-government officials’ liability in Russia as well as the increasing gap between the population and local self-government, uncertainty of legal solutions and enforcement practice. Members of the expert community, municipalities and practitioners have high hopes for the new legal framework in the field of local self-government, which is being developed following the amendments to the Constitution of the Russian Federation in 2020. As a result, strengthening and expansion of local self-government powers are expected, which will increase citizens’ involvement in resolving issues of local importance. However, draft law No. 40361-8 on local self-government submitted to the State Duma on December 16, 2021, provides for the liquidation of the settlement level and the reduction in the number of lower-level local self-government bodies. As a result, the gap between the population and local self-government bodies has highly increased. In addition, the draft law strengthened responsibility of the heads of municipalities to the highest officials of the constituent entities of the Russian Federation, which implies more dependence of lower-level authorities on the state.Conclusion. Legislation is rapidly adjusting to the existing realities rather than establishing a legal basis for local self-government development. In order to restore the essence of local self-government, deformed as a result of systematic changes in the legal basis of local self-government, it is necessary to improve the submitted bill, strengthening local self-government as a factor in the sustainable development of a democratic Russian state.